Analysis of physical condition components of petanque athletes - Ariyanto, Arsan Firdaus; Yuliastrid, Dita; Wahyudi, Heri; Susanto, Indra Himawan (Sriwijaya Journal of Sport, 2026)
Research Problems: Physical condition is a fundamental component supporting performance in precision sports such as petanque. Optimal endurance, balance, strength, and flexibility are required to maintain stability, accuracy, and consistency during competition. However, empirical data regarding the physical condition profile of petanque athletes remains limited. Research Objectives: This study aimed to analyze the physical condition components of petanque athletes. Methods: This research employed a descriptive quantitative design involving 24 athletes selected using a total sampling technique. The instruments used were the Queen’s College Step Test (endurance), Standing Stork Test (balance), Handgrip Strength Test (strength), and Static Flexibility Test – shoulder and wrist (flexibility). Data were analyzed using descriptive statistics in the form of frequencies and percentages. Results: The results showed that endurance levels were categorized as very poor (33.3%), poor (8.3%), moderate (33.3%), good (20.8%), and very good (4.2%). Balance levels were very poor (4.2%), poor (8.3%), moderate (16.7%), good (33.3%), and very good (37.5%). Strength levels were very poor (25.0%), poor (29.2%), moderate (29.2%), good (16.7%), and none reached the very good category (0%). Flexibility levels showed that 100% of athletes were in the very good category. Conclusion: In conclusion, the physical condition profile indicates that balance and flexibility components are relatively well-developed, while endurance and strength require further improvement. These findings can serve as baseline data for designing more structured and targeted training programs to enhance athletes’ physical performance.